KKN TEMATIK MAHASISWA UMSU DALAM PENGEMBANGAN DESA WISATA DI DESA SUKA MAKMUR - Dewi Pujiawati; Aisyah Balqish, Amanda Sukmawati, Edisah Putra Nainggolan (JOURNAL OF COMMUNITY DEDICATION, 2024)
Community Service Program (KKN) is a community empowerment activity by students that aims to develop tourism potential. In Deli Serdang Regency, particularly in Suka Makmur Village, KKN applies the concept of 5A (Attractions, Accessibility, Amenities, Activities, Accommodation) and SAPTA PESONA (security, order, cleanliness, coolness, beauty, friendliness, memories). Through a descriptive qualitative approach, the program succeeded in raising community awareness about the importance of tourism and providing training in tourism destination management. The result is increased community participation and the emergence of new business units that support the local economy. With the support of the village government and the active involvement of the community, the development of tourism villages shows promising prospects despite facing challenges in terms of budget and coordination between stakeholders.